Early biomarkers of extracapsular extension of prostate cancer using MRI-derived semantic features - Guerra, Adalgisa (2022)
Funding This work is supported by a PhD student scholarship (Adalgisa Guerra) it was granted as a scientifc project by Hospital da Luz (ID LH.INV.F2019027). Helena Mouriño was supported by CEAUL (funded by FCT, Portugal, through the project UIDB/00006/2020).